Report on proposed new interior design scheme of YDP Agong Gallery for Arkib Negara Malaysia at Lot 2325, Jalan Dato’ Onn, 50480, Kuala Lumpur, Malaysia / Mohd Shahid Jamahuri - Jamahuri, Mohd Shahid (Faculty of Architecture, Planning and Surveying, 2010)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a proposed new interior design scheme of Yang Di Pertuan Agong Gallery for Arkib Negara Malaysia at Lot 2325, Jalan Dato Onn, 50480 Kuala Lumpur. With the outcome of a national history gallery and information source of Malaysian royal institution, it is hope to make Arkib Negara Malaysia get more appreciation because always keep the responsibilities in concerning and care about national history and precious belonging treasures. The concept and image is also apply to both interior and exterior to appeal the centre will be able to lure more tourists and visitors who were always keen in our aesthetic values in architecture. There were several researches done to succeed this tourist information centre final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Arkib Negara Malaysia demands in terms of function and aesthetic value.